The Eight National Information Day: Open Science, Open Data, Open Access - Peter L. Stanchev; Zlatina Karova; Yanita Zherkova; Radoslav Pavlov; George Simeonov (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2017)
The paper draws current state of Bulgarian Open access (OA) activities and discussion points for the Eight National Information Day: Open Science, Open Data, and Open Access